(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article briefly examines modern approaches to applying artificial intelligence (AI) methods to automated quality assessment of precious and ornamental stones (identification, origin determination, treatment detection, and 4C grading), as well as the potential of generative and auxiliary AI tools in jewelry design. Key algorithmic approaches (computer vision, convolutional neural networks, multimodal architectures, and spectral data processing methods) are discussed, along with case studies and commercial solutions, as well as issues of validation, standardization, and ethics. A review of key literature and practical results is provided.